EXAMINATION OF GOVERNMENT POLICIES THAT ADDRESS TACIT KNOWLEDGE SHARING AND HOW WELL THESE POLICIES HAVE BEEN APPLIED AND FORTIFIED TO ENHANCE PUBLIC SECTOR PERFORMANCE. - Njeri, Wamitu Susan (Machakos University, 2019)
Knowledge is an integral part of the factors that impact growth in an economy; more so in this knowledge age. Both public and private sector enterprises have embraced the knowledge concept, through not only harnessing the knowledge that abounds, but also managing it as they also ascertain that it is shared. Out of the numerous facets of knowledge, the most elusive and difficult to share is tacit knowledge, yet it highly impacts performance of organisations. The public sector generates and is also exposed to a lot of knowledge which in most cases is acquired but rarely shared. In the Kenyan civil service, there seems to be ignorance in the following areas: the amount of knowledge that flows through the Kenyan civil service every day, accounting for the knowledge that the Kenyan civil servants require for present and future needs, how to acquire that knowledge, the kind of knowledge that individual employees in the civil service possess and how to share such knowledge so as to enhance public sector performance. This situation then begs the question: are there tacit knowledge sharing policies in the Kenyan civil service and if there are how are they applied and fortified to enhance public sector performance?
Keywords: Knowledge; Tacit knowledge; Public sector; Civil servants; Performance